2020
DOI: 10.1136/jnnp-2019-322242
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive inhibition impairments in presymptomatic C9orf72 carriers

Abstract: ObjectiveTo investigate cognitive inhibition in presymptomatic C9orf72 mutation carriers (C9+) and its associated neuroanatomical correlates.MethodsThirty-eight presymptomatic C9orf72 mutation carriers (C9+, mean age 38.2±8.0 years) and 22 C9− controls from the PREV-DEMALS cohort were included in this study. They underwent a cognitive inhibition assessment with the Hayling Sentence Completion Test (HSCT; time to completion (part B−part A); error score in part B) as well as a 3D MRI.ResultsC9+ individuals young… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 52 publications
2
11
0
Order By: Relevance
“…When looking at single genetic alterations, we identified gMND and, particularly, C9-MND as driving these results, which are consistent with recent studies indicating the involvement of the cognitive/affective regions of the posterior cerebellum (particularly, lobule VII and crus regions, involved in the modulation of emotions and social behaviors) as indicative of the presence of a C9orf72 mutation, 7 possibly as a consequence of the close structural and functional connections with the thalami through cerebello-thalamo-cortical networks. 42 , 45 Similar alterations have been demonstrated in presymptomatic C9orf72 mutation carriers, 37 , 38 , 46 correlating with cognitive inhibition deficits. 46 Although the role in cognition and the topologic organization of the cerebellar cortex has started being elucidated only in recent years, 45 this is an exciting area of developing research for biomarkers of disease pathology in the FTLD spectrum (including MND) that might be combined with other more established measures of cortical damage.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…When looking at single genetic alterations, we identified gMND and, particularly, C9-MND as driving these results, which are consistent with recent studies indicating the involvement of the cognitive/affective regions of the posterior cerebellum (particularly, lobule VII and crus regions, involved in the modulation of emotions and social behaviors) as indicative of the presence of a C9orf72 mutation, 7 possibly as a consequence of the close structural and functional connections with the thalami through cerebello-thalamo-cortical networks. 42 , 45 Similar alterations have been demonstrated in presymptomatic C9orf72 mutation carriers, 37 , 38 , 46 correlating with cognitive inhibition deficits. 46 Although the role in cognition and the topologic organization of the cerebellar cortex has started being elucidated only in recent years, 45 this is an exciting area of developing research for biomarkers of disease pathology in the FTLD spectrum (including MND) that might be combined with other more established measures of cortical damage.…”
Section: Discussionsupporting
confidence: 64%
“… 42 , 45 Similar alterations have been demonstrated in presymptomatic C9orf72 mutation carriers, 37 , 38 , 46 correlating with cognitive inhibition deficits. 46 Although the role in cognition and the topologic organization of the cerebellar cortex has started being elucidated only in recent years, 45 this is an exciting area of developing research for biomarkers of disease pathology in the FTLD spectrum (including MND) that might be combined with other more established measures of cortical damage.…”
Section: Discussionsupporting
confidence: 64%
“…In the HSCT, participants are asked to complete 15 sentences using the appropriate word, as fast as possible (automatic condition, Part A), and 15 sentences using a completely unrelated word (inhibition condition, Part B). Recently, it has been demonstrated that this test is a reliable measure of cognitive inhibition impairments in pre‐symptomatic C9orf72 mutation carriers and their proximity to clinical conversion to bvFTD 14 . We used the Hayling error score (number of errors in Part B) as a measure of the difficulty to inhibit a prepotent response, as in Flanagan et al 15 .…”
Section: Methodsmentioning
confidence: 99%
“…An example of specific C9orf72 -related impairment is the presence, in pre-symptomatic carriers, of deficits in cognitive inhibition (i.e., the ability to resist to interference from irrelevant stimuli) which seems to become more evident in individuals who are closer to symptom onset [ 40 ]. Some other studies have shown the presence of deficits in semantic access [ 41 ] as well as early involvement of praxis, which has been observed already in subjects younger than 40 years of age, supporting the hypothesis that frontal and prefrontal structures are early involved in degeneration [ 42 ].…”
Section: Biomarkers and Outcome Measuresmentioning
confidence: 99%